PUYW: Uma ontologia para o gerenciamento de perfis de aprendiz integrando YouTube e Wikipédia para apoiar um sistema de recomendação ubíqua de conteúdos - Bezerra , Sidney D. F.; M. Neto , Francisco M.; Monteiro , Bruno S.; Silva , Salatiel D.; Silva , Patrício A.; Costa, Antônio V. T. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
Recommendation systems have become an increasingly present element in the purpose of detecting and recommending important features to users. The challenge in such systems is to present information that is in accordance with interest of the user. For that, they make use of techniques for filtering content to associate them to users. In this sense, this article aims to demonstrate an ontology called Profiler User YouTube Wikipedia, which aims to represent and store users´ information, and their digital traits relative to their preferences about videos, channels, YouTube playlists and Wikipedia texts. This ontology will support the Youubi recommendation system in the search and selection of content associated with the characteristics of the learner.